Split-disk properties of kenaf yarn fibre-reinforced unsaturated polyester composites using filament winding method - Misri, Sairizal; Ishak, Mohamad Ridzwan; Salit, Mohd Sapuan; Leman, Zulkiflle (Universiti Putra Malaysia Press, 2016)
There are many contributions from synthetic fibres in the world of industrial composites over the years. However, they contain hazardous properties to humans causing irritation when exposed to the skin and eye. Inhalation of fibrous synthetic can cause lung cancer with its deadly effects. There have been studies and researches conducted on natural fibres to replace synthetic fibres as it is believed the latter are more environmental-friendly and pose less health risks to humans. The aim of this study was to investigate hoop tensile properties of the composite hollow shaft for different winding angles and PVC reinforcement produced via the filament winding technique. For this purpose, split-disk tests (according to ASTM D-2290 standard) were performed for the specimens produced with two different winding angles such as 45o and 90o winding angle. By determining the hoop tensile strength and modulus of these specimens, the effects of filament-winding processing parameter in winding angle were evaluated. Experiments successfully showed that the mechanical properties such as tensile properties of kenaf yarn fibre reinforced unsaturated polyester hollow tube at 90° and 45° winding angle with and without PVC. The value was 15% for the different winding angles and 25% for the different winding angles with and without PVC. The results indicate that 90° fibre winding angle kenaf yarn fibre unsaturated polyester with PVC has the highest hoop tensile strength compared with other composite specimens. The experiments concluded that the orientation on fibre angle has a significant impact on the hoop tensile strain, hoop tensile modulus and hoop tensile strength properties.